2017
DOI: 10.1016/j.lungcan.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous resistance mechanisms in an EGFR exon 19-mutated non-small cell lung cancer patient treated with erlotinib: Persistent FGFR3 -mutation, localized transformation to EGFR -mutated SCLC, and acquired T790M EGFR -mutation

Abstract: Patients with epidermal growth factor receptor (EGFR) gene-mutated non-small cell lung cancer (NSCLC) obtain substantial clinical benefit from EGFR tyrosine-kinase inhibitors (TKIs), but will ultimately develop TKI-resistance resulting in median progression-free survival of 9-15 months during first-line TKI-therapy. However, type and timing of TKI-resistance cannot be predicted and several mechanisms may simultaneously/subsequently occur during TKI-treatment. In this respect, we present a 49 year-old Caucasian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 12 publications
4
30
0
Order By: Relevance
“…Additionally, lung ADC may contain oncogenic FGFR3-TACC3 fusions that may function as bypass-mechanism associated with intrinsic/acquired resistance to EGFR-TKIs reversible by FGFR-inhibitors [ 54 56 ]. As we recently described elsewhere, our advanced EGFR -mutant ADC-case with concomitant FGFR3 -mutation displayed mixed response, with pleural metastasis progressing already 7 weeks after initiating first-line erlotinib-treatment, whereas other metastatic sites progressed only 6 months later after acquiring additional p.T790M EGFR -mutation [ 57 ].…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, lung ADC may contain oncogenic FGFR3-TACC3 fusions that may function as bypass-mechanism associated with intrinsic/acquired resistance to EGFR-TKIs reversible by FGFR-inhibitors [ 54 56 ]. As we recently described elsewhere, our advanced EGFR -mutant ADC-case with concomitant FGFR3 -mutation displayed mixed response, with pleural metastasis progressing already 7 weeks after initiating first-line erlotinib-treatment, whereas other metastatic sites progressed only 6 months later after acquiring additional p.T790M EGFR -mutation [ 57 ].…”
Section: Discussionmentioning
confidence: 78%
“…This study suggested the contribution of FGFR3 signaling to T790M-mediated erlotinib resistance in lung cancer patients. 109 In addition, treatment with FGFR inhibitors restored the sensitivity to EGFR-TKIs in primary drug-resistant SCLC cells. 110 Therefore, FGFR activation is one of the possible causes of developed resistance to EGFR-TKIs in lung cancer patients.…”
Section: Fibroblast Growth Factor Receptor Signalingmentioning
confidence: 99%
“…Caucasian male ex-smoker with metastasized pulmonary ADC harboring an EGFR exon 19 deletion and an unreported 2-bp frame-shift microdeletion in FGFR3 showed transformation from ADC to SCLC within 7 weeks of the initiation of erlotinib treatment. 109 Further, following the completion of six cycles of erlotinib treatment, an additional EGFR T790M mutation appeared which caused erlotinib resistance. This study suggested the contribution of FGFR3 signaling to T790M-mediated erlotinib resistance in lung cancer patients.…”
Section: Fibroblast Growth Factor Receptor Signalingmentioning
confidence: 99%
“…Several studies have reported transient response to EP regiments after the development of SCLC transformation. 17,18 Here, we reported an unexpected case of a favorable response to EP of an EGFR-mutant patient who developed SCLC transformation as resistance to erlotinib with a PFS of 7.7 months.…”
Section: Discussionmentioning
confidence: 93%
“…9,10 Numerous studies have documented such cases. [15][16][17] Most patients who developed SCLC transformation are often associated with aggressive clinical behaviors and poor prognosis with a median overall survival (OS) of 6 months. Several studies have reported transient response to EP regiments after the development of SCLC transformation.…”
Section: Discussionmentioning
confidence: 99%